TINGKAT PENGETAHUAN PETANI DALAM KEGIATAN BUDIDAYA TANAMAN JAGUNG MANIS DI DESA AMESIU KECAMATAN PONDIDAHA KABUPATEN KONAWE - Mahdin; Anas Nikoyan; Yoenita Jayadisastra (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2024)
Farmers in Amesiu Village, Pondidaha Sub-district, Konawe Regency have difficulty in achieving productivity levels due to the lack of knowledge of farmers in conducting effective and efficient sweet corn cultivation activities. The purpose of this study was to determine the level of knowledge of farmers in sweet corn cultivation activities. The technique of determining informants in this study using snowball sampling technique with the number of informants 17 people. Data collection techniques in this research are observation, in-depth interviews, documentation and literature. Data analysis in this study is descriptive qualitative conducted specifically to determine the level of knowledge of farmers by describing the level of knowledge of farmers consisting of remembering, understanding, applying, applying and evaluating. The results showed that farmers' knowledge in sweet corn cultivation activities was at the level of remembering, understanding, applying and evaluating but not yet at the level of analyzing.